The double metamagnetic phase transition in an ising antiferromagnet with light-plane single-ion anisotropy and with ion spin S = 1 - Lavanov, G.Yu. (Reports of the National Academy of Sciences of Ukraine, 2018)
It is shown that, in an Ising AFM with ion spin S = 1, a magnetic field at T ≠ 0 can induce a double metamagnetic transition in the form of a sequence of two quantum first-order magnetic phase transitions (QPT I) from a plateau in the magnetization between these transitions. In this case, the transition from the antiferromagnetic phase to the ferromagnetic phase occurs through the intermediate state formation, in which the sublattice spin initially magnetized against the magnetic field is in the Van Vleck paramagnetic state.